Membangun Mindset Produktif dan Kreatif dalam Mengelola Keuangan untuk Kewirausahaan Siswa - Saniatul Mahbuba; Amelia .; Berliana Nur Cahyani (CV. ITTC INDONESIA, 2026)
Financial management skills are a crucial aspect in fostering the entrepreneurial spirit of vocational school students. However, many students still have a consumptive financial management pattern and the mistaken belief that entrepreneurship requires large capital. This community service activity aims to foster a productive and creative mindset in financial management for Media Informatika Vocational School students as a foundation for entrepreneurship. The methods used include interactive workshops, daily financial management simulations, group discussions, and mentoring in developing simple business plans. The target group is 30 12th-grade students. The results of the activity indicate an increase in students' understanding of the importance of financial management, a shift from a consumptive to a productive mindset, and increased interest and courage in starting small businesses with realistic financial calculations. This activity confirms that a practical and contextual approach is effective in developing an entrepreneurial mindset in vocational school students.